Synthesis of 2-Arylbenzothiazol-5-amines from N,N-Dialkyl-3-nitroanilines - Pham, Hang T.; Ho, Tuan H.; Do, Duy Q.; Nguyen, Kim L. H.; Nguyen, Tung T.; Phan, Nam T. S. (Synlett, 2020)
We report a simple method for coupling of N,N-dialkyl-3-nitroarenes, elemental sulfur, and activated sp3 C–H bonds in 2-methylazaarenes or arylacetic acids to afford derivatives of 2-arylbenzothiazol-5-amines. Only DABCO base was required, and many heterocycles such as imidazoles, oxazoles, quinolines, and thiophenes were compatible with the reaction conditions. Our approach offers a simple route to useful substituted thiazol-5-amines from commercially available nitroarenes.
Keywords: Key words; dialkylnitroanilines; sulfur; benzothiazolamines; heterocycles; multicomponent reaction